Utilization of Interactive Learning Media in Teaching Jinayat Fiqh Material at MAN 3 Medan - Amini, Shafa Rasmi; Setiawan, Hasrian Rudi (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the utilization of interactive learning media in teaching jinayat fiqh material to students at MAN 3 Medan. Jinayat fiqh, as a branch of Islamic law dealing with criminal acts and their punishments, contains abstract and complex concepts that require innovative learning strategies to be effectively understood by students. This research employed a descriptive qualitative design with data collected through observation, interviews, and documentation. The findings indicate that the use of interactive learning media—such as animated videos, case simulations, and dynamic presentations—significantly enhances students’ understanding of jinayat fiqh concepts. Moreover, interactive media also improve students’ enthusiasm, participation, and analytical skills when examining Islamic legal cases. The study concludes that the application of interactive learning media is highly effective in assisting teachers to deliver jinayat fiqh material in a more engaging and comprehensible manner.